IMPLEMENTATION OF THE GOVERNMENTAL QUALITY ASSURANCE SYSTEM IN UKRAINE - Красников, Євген; Калита, Петро (Київський національний університет імені Тараса Шевченка, 2025)
B a c k g r o u n d . Nowadays, Ukraine's defense and security sector is undergoing fundamental reforms in the procurement of defense products, particularly in the field of quality assurance of such products through the assessment of quality management systems within the framework of Governmental Quality Assurance (GQA) actions. These reforms require both theoretical and methodological justification regarding the directions of such changes and the mechanisms for their implementation. An important issue is the establishment of unified terminology in the field of quality management and management in general, harmonized with the corresponding terminology of EU and NATO member states. The full-scale invasion of russia into Ukraine has brought to the forefront issues related to the implementation of a governmental quality assurance system. The goal of the study is to analyze the Soviet quality control system and compare it with the state quality assurance system, as well as to justify the establishment of modern management systems in Ukraine. M e t h o d s . The study employed methods such as analysis, synthesis, and generalization, through which proposals for establishing a new system for ensuring the quality of defense-related products were developed and substantiated. R e s u l t s . In the course of the research, the state of the quality control system for defense products was analyzed, specifically itsorganizational structure, regulatory framework, and capacity to ensure product quality under modern conditions. The study also examined the state quality assurance system according to the following components: structure, scope of work, documentation, and training of specialists. Possible mechanisms of interaction between these systems were explored at the level of individual elements. A significant part of the research addressed issues of terminological inconsistency and conceptual frameworks in the field of management and quality management, taking into account the specific characteristics of the defense sector. C o n c l u s i o n s . An institutional approach was applied to analyze the existing quality control system and the state quality assurance system. The main directions for implementing a modern quality assurance system in the defense sector were identified. This system should be based on a risk-oriented approach and the evaluation of quality management processes within enterprises supplying defense-related products.

В с т у п . Сьогодні у сфері безпеки й оборони України здійснюються масштабні реформи механізмів закупівлі продукції оборонного призначення, зокрема в частині забезпечення якості такої продукції шляхом проведення оцінювання системи менеджменту якості підприємств постачальників у межах проведення робіт із державного гарантування якості. Ці реформи вимагають теоретико-методичного обґрунтування як шляхів таких змін, так і механізмів їх здійснення. Важливим питанням є визначення єдиної термінології у сфері менеджменту якості та менеджменту загалом, яка була б гармонізована з відповідною термінологією держав-членів ЄС та НАТО. Повномасштабне вторгнення росії в Україну актуалізувало розгляд питань, пов'язаних із запровадженням системи державного гарантування якості. Мета дослідження полягає в аналізі радянської системи контролю якості та порівнянні її із системою державного гарантування якості. М е т о д и . У дослідженні були використані такі методи, як аналіз, синтез, узагальнення, за допомогою яких опрацьовані й обґрунтовані пропозиції щодо формування нової системи забезпечення якості продукції оборонного призначення. Р е з у л ь т а т и . Проаналізовано стан системи контролю якості продукції оборонного призначення, зокрема організаційної структури цієї системи, її нормативного регулювання та спроможності забезпечити якість продукції в сучасних умовах. Досліджено системи державного гарантування якості за такими складниками, як структура, склад робіт, документація, підготовка фахівців, а також можливі механізми взаємодії зазначених систем за окремими елементами. В и с н о в к и . Застосовано інституціональний підхід з питань аналізу чинної системи контролю якості та системи державного гарантування якості. Визначено основні напрями запровадження у сфері оборони сучасної системи забезпечення якості, яка базується на ризик-орієнтованому підході.
УПРОВАДЖЕННЯ В УКРАЇНІ СИСТЕМИ ДЕРЖАВНОГО ГАРАНТУВАННЯ ЯКОСТІ
Keywords: quality control; quality assurance; management; standards; quality management system; defense; procurement; AQAP; risk management; standardization; контроль якості; гарантування якості; стандарти; система менеджменту якості; оборона; закупівлі; AQAP; управління ризиками; стандартизація